Switching to the anti-interleukin-6 receptor antibody tocilizumab in rheumatoid arthritis patients refractory to antitumor necrosis factor biologics - Kawashiri, Shin-ya; Kawakami, Atsushi; Iwamoto, Naoki; Fujikawa, Keita; Aramaki, Toshiyuki; Tamai, Mami; Arima, Kazuhiko; Ichinose, Kunihiro; Kamachi, Makoto; Yamasaki, Satoshi; Nakamura, Hideki; Origuchi, Tomoki; et al. (Modern rheumatology, 2010)
Abstract We evaluated the short-term effects of the anti-interleukin-6 (IL-6) receptor antibody tocilizumab (TCZ) in six patients with rheumatoid arthritis (RA) who had been refractory to tumor necrosis factor (TNF) antagonist therapy. All subjects were considered to be secondary nonresponders to TNF antagonists as decided by each physician. The Disease Activity Score of 28 Joints (DAS28) appeared to improve slowly by TCZ compared with TNF antagonist therapy, but significantly decreased at 24 weeks. One patient achieved DAS28 remission [DAS28-erythrocyte sedimentation rate (ESR) <2.60, and 5 of 6 patients showed good or moderate clinical response. The change in the clinical Disease Activity Index was similar to that of the DAS28-ESR. The serum level of matrix metalloproteinase-3 (MMP-3), a marker for synovial overgrowth, also significantly decreased after the treatment (518 ± 567 at baseline, 141 ± 90 ng/ml at 24 weeks, p < 0.05). One patient discontinued TCZ because of tuberculous peritonitis. Although physicians need to watch for infectious adverse events, these data indicate that TCZ is effective for treating RA patients refractory to TNF antagonists.